Modelling Methodology as the Basis for Implementation of an Interdisciplinary Approach in the Training of Students of Pedagogical Specialties - E. A. Perminov; V. A. Testov (Образование и наука)
Introduction. Nowadays, according to the tendencies of education modernisation, an interdisciplinary approach is taking a leading role, based on deepening the links between education and science, which is the most acute problem in the conditions of large amounts of scientific information. The implementation of the interdisciplinary approach is based on the methodology of modelling using information technologies, as a methodology of a new post-industrial stage of scientific culture of research in the digital age, which is of fundamental importance in modern teacher training.The aim of the present article is to investigate the aspects of modelling methodology using information technologies in the implementation of an interdisciplinary approach in the training of students of pedagogical specialties.Methodology and research methods. In the course of the research, a modelling methodology, a systematic approach, the analysis and generalisation of the results of academic works on the implementation of interdisciplinary, cultural, and meta-subject approaches in education were employed.Results and scientific novelty. The authors conducted the analysis of interdisciplinary approach (interdisciplinary integration) as a leading trend in post-industrial education. It is justified that interdisciplinary training, implemented on the basis of modelling methodology, is of fundamental importance in the formation of general-cultural scientific ideas among students and in their awareness of science as the ideal scientific knowledge. Various aspects of modernisation of teacher training based of modelling methodology are investigated. The main peculiarities of implementation of cultural and meta-subject approaches in the selection of the content of profile training of future teachers are identified. It is revealed that interdisciplinary courses play an important role in the implementation of the interdisciplinary approach. The didactic and methodological principles for the development of model-theoretical interdisciplinary courses for future teachers are established. It is demonstrated that in accordance with the modelling methodology, the main didactic goal of such courses is to teach the implementation of stages for investigating solutions of research problems (objects of processes or phenomena) using information technologies.Practical significance. The materials of the article contribute to the implementation of the interdisciplinary approach in the content of training of students of pedagogical specialties. Also, the research findings might be useful for both theorists of education and for teachers, who are engaged in professional training of students of pedagogical specialties, and all those who are interested in the further development of educational system.